Multicenter evaluation of independent high-throughput and RT-qPCR technologies for the development of analytical workflows for circulating miRNA analysis - Babayan, Anna; Loges, Sonja (Cancers, 2020)
Background: Among emerging circulating biomarkers, miRNA has the potential to detect lung cancer and follow the course of the disease. However, miRNA analysis deserves further standardization before implementation into clinical trials or practice. Here, we performed international ring experiments to explore (pre)-analytical factors relevant to the outcome of miRNA blood tests in the context of the EU network CANCER-ID. Methods: Cell-free (cfmiRNA) and extracellular vesicle-derived miRNA (EVmiRNA) were extracted using the miRNeasy Serum/Plasma Advanced, and the ExoRNeasy Maxi kit, respectively, in a plasma cohort of 27 NSCLC patients and 20 healthy individuals. Extracted miRNA was investigated using small RNA sequencing and hybridization platforms. Validation of the identified miRNA candidates was performed using quantitative PCR. Results: We demonstrate the highest read counts in healthy individuals and NSCLC patients using QIAseq. Moreover, QIAseq showed 15.9% and 162.9% more cfmiRNA and EVmiRNA miRNA counts, respectively, in NSCLC patients compared to healthy control samples. However, a systematic comparison of selected miRNAs revealed little agreement between high-throughput platforms, thus some miRNAs are detected with one technology, but not with the other. Adding to this, 35% (9 of 26) of selected miRNAs in the cfmiRNA and 42% (11 of 26) in the EVmiRNA fraction were differentially expressed by at least one qPCR platform; about half of the miRNAs (54%) were concordant for both platforms. Conclusions: Changing of (pre)-analytical methods of miRNA analysis has a significant impact on blood test results and is therefore a major confounding factor. In addition, to confirm miRNA biomarker candidates screening studies should be followed by targeted validation using an independent platform or technology.
Gesehen am 19.10.2020